Analisis Potensi Kecelakaan Kerja Kegiatan Bongkar Muat Peti Kemas Pada Pekerja Di Terminal Peti Kemas Makassar - Muchlisa Ibnu; Ganding Sitepu; Misliah Idrus (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
This study aims to identify, determine, and control sources of danger that can cause work accidents at container ports which can be caused by container loading and unloading activities from ships to Container Yards. The research method used is quantitative using questionnaires, observations, and interviews as research instruments. The research sample was 116 workers involved in container loading and unloading activities at the port. The results of the study show that the level of implementation of the Occupational Safety and Health Management System (SMKK) in ports is still lacking and needs to be improved. The recommended hazard source control strategy is ensuring activities are carried out by experienced operators, providing training to operators, and checking and maintaining the unit so that it is in a proper operating condition. This research is expected to contribute to the development of occupational safety and health at container ports.